O lambadão de Mato Grosso : registros de uma dança popular urbana - Fontes, Tânia Aparecida de Oliveira (2012)
The pace lambadão, in his dancing representation, he was elected as a research object of this study. The problem raised by this research suggests that the lambadão, while popular manifestation, can no longer be considered as a mere "foot" popular, as happened with his namesake lambada. This rate appeared approximately 20 years, today, shows that increasingly the practice space conquest, supporters and a community representative of the consumer "products and services" linked to the rhythm. The methodology chosen was the Ethnographic research that sought various reasons and authors, such as concepts: concept of culture and ethnographic fieldwork in the studies of Geertz, Laraia, Malinowski, Magnani, Cardoso, Lévi-Strauss, Canevacci; Popular culture: understood by Hall, Brandão, Silva, Gabriel; Mato Grosso culture: represented by Loureiro, Grando, Arruda; Dance while thought, defended by Katz, among others. As chance presented the lambadão, in its early days, has received influences from other popular rhythms, among them the Rasqueado regional and the Siriri, joined to other northern Brazilian rhythms, as the Carimbó. We seek to launch a different look on the rhythm, here understood as a way of thinking, filled with quirky elements themselves and that has been built over the last two decades. In this way, we believe that our research has a directory object itself, which is made up of numerous practices intra and extra dance, added the specific body elements. All of these components together identifies it in regional cultural scenario and further enhances the diffusion of this popular manifestation of downloaded cuiabana and adjacencies. The study was to observe, analyse and codify this vocabulary and peculiarities as unique as thought-provoking.